2013
DOI: 10.1108/ijpdlm-11-2011-0201
|View full text |Cite
|
Sign up to set email alerts
|

Modeling overbookings on air cargo transportation

Abstract: PurposeIn order to hedge against fluctuation in actual “show” for air freight services, cargo airlines engage in the allocation of more space capacity than they actually have. This practice can lead to overbooking of capacity which can incur costs to the airline when a cargo does show that is larger than predicted. In this study, the authors set out to model an optimised value for air cargo booking which is tested against five different cargo case‐representative scenarios. The paper aims to discuss these issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Similarly, a fuzzy reasoning model used the same parameters to obtain overbooking levels (Wang & Kao, 2008). Furthermore, it has been indicated that cancellation rates and shipping information records should be added to these parameters in overbooking calculations (Chalermkiat et al, 2013). Additionally, Kasilingam (1997a) discussed the difference between passenger and cargo overbooking as a revenue management tool.…”
Section: Air Cargo Capacity Management and Allocationmentioning
confidence: 99%
“…Similarly, a fuzzy reasoning model used the same parameters to obtain overbooking levels (Wang & Kao, 2008). Furthermore, it has been indicated that cancellation rates and shipping information records should be added to these parameters in overbooking calculations (Chalermkiat et al, 2013). Additionally, Kasilingam (1997a) discussed the difference between passenger and cargo overbooking as a revenue management tool.…”
Section: Air Cargo Capacity Management and Allocationmentioning
confidence: 99%
“…Scientific methods have been successfully used to improve revenue management in the commercial airline industry (Singhaseni et al, 2013;Rose, 2016;Yeoman, 2016). One of those improved areas is in seat pricing and allocation (see Singhaseni et al, 2013;Lan et al, 2015;Hjorth et al, 2018;Ko, 2019).…”
Section: Overbooking and Revenue Managementmentioning
confidence: 99%
“…Scientific methods have been successfully used to improve revenue management in the commercial airline industry (Singhaseni et al, 2013;Rose, 2016;Yeoman, 2016). One of those improved areas is in seat pricing and allocation (see Singhaseni et al, 2013;Lan et al, 2015;Hjorth et al, 2018;Ko, 2019). Commercial airlines will reserve airline seats in excess of their existing capacity (overbooking) as a way to counter the loss of revenue from 'no shows', late cancellations, and early and/or late departures.…”
Section: Overbooking and Revenue Managementmentioning
confidence: 99%
“…The healthcare industry overbooks doctors' time which can lead to increased waiting time for customers and physician overtime costs when all patients arrive for their appointments (Zacharias & Pinedo, 2013). Airlines have been known to overbook seats (Coughlan, 1999) and cargo space (Singhaseni, Wu, & Ojiako, 2013). When more customers show up than predicted, they are typically moved to another flight which causes delays and other inconveniences for the customer.…”
Section: Oversubscription In Other Industriesmentioning
confidence: 99%